System for evaluating powerlifting and other multievent performances - Bishop, P. A.; Williams, T. D.; Heldman, A. N.; Vanderburgh, P. M. (The Journal of Strength and Conditioning Research, 2018)
Currently, the sport of powerlifting discriminates against bench press scores and uses an empirical equation which is very difficult to update to determine the best lifter within sex. The purpose of this study was to provide a simple and statistically sound method for evaluating powerlifting performance which could also be used with other multievent sports. Data were collected from a large public database on the top 50 (men) or the top 30 (women) individual raw competition scores in each weight class for each of the 3 powerlifting lifts. Mean and SDs were then calculated for each lift and weight class by sex. Powerlifting performance was evaluated by the sum of the 3 z-scores for the 3 lifts divided by 3 (the highest score wins). The z-scores reflect a dimensionless number which can be used to evaluate each lift and the total of the 3 lifts across weight classes and between sexes. Although the mean and SDs should be relatively stable, this computation is transparent and can be readily updated as lifters improve. This system overcomes the bias against bench press and many of the measurement challenges in evaluating athletes in multievent sports, in multiple weight divisions, and between sexes. These findings can benefit coaches and athletes by allowing simpler evaluations of performance and improvement.